2020
DOI: 10.1177/0300060520971445
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute pulmonary embolism in patients with off-pump coronary artery bypass grafting: implications for nursing

Abstract: Objective Acute pulmonary embolism (APE) is a serious complication after off-pump coronary artery bypass grafting (OPCABG). We aimed to analyze the risk factors for APE in patients with OPCABG. Methods In this retrospective, observational study, patients with OPCABG who were treated in our hospital from 1 January 2018 to 31 March 2020 were included. The basic characteristics of patients and results of preoperative laboratory examinations were collected and analyzed. Results A total of 707 patients with OPCABG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Prior research has identified various risk factors for PE following OPCABG, with a primary focus on a patient’s medical history and the circumstances before or during surgery. Zhou et al 14 found that factors such as ejection fraction, smoking history, number of grafts, surgery duration, and age were associated with an increased risk of acute PE after OPCABG. Du et al 15 reported that a history of bleeding disorders, congestive heart failure in the 30 days leading up to surgery, and surgery lasting over 310 minutes were linked to a higher likelihood of venous thromboembolism after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has identified various risk factors for PE following OPCABG, with a primary focus on a patient’s medical history and the circumstances before or during surgery. Zhou et al 14 found that factors such as ejection fraction, smoking history, number of grafts, surgery duration, and age were associated with an increased risk of acute PE after OPCABG. Du et al 15 reported that a history of bleeding disorders, congestive heart failure in the 30 days leading up to surgery, and surgery lasting over 310 minutes were linked to a higher likelihood of venous thromboembolism after CABG.…”
Section: Discussionmentioning
confidence: 99%